1987
DOI: 10.1017/s0007485300011561
|View full text |Cite
|
Sign up to set email alerts
|

Survey of enzyme variation in british populations of Myzus persicae (Sulzer) (Hemiptera: Aphididae) on crops and weed hosts

Abstract: Electrophoretic variation of eight enzymes (thirteen loci) including esterase-4 (EST-4, the enzyme conferring insecticide resistance) was studied in clones of Myzus persicae (Sulzer) from several localities in south-eastern England (major beet and rape growing areas) and from a site in mid-Scotland (a seed potato growing region). All loci except esterase-l/-2, which showed putative allelic variation with slow (EST-1) and fast (EST-2) bands, and EST-4, which occurred as three principal quantitative variants (su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…However, aphid allozyme studies have revealed low levels of genetic polymorphism and correspondingly low levels of heterozygosity (Tomiuk & Wöhrmann, 1980; Loxdale et al. , 1985; Brookes & Loxdale, 1987; Tomiuk, 1987; Loxdale & Brookes, 1988, 1990; Simon & Hebert, 1995; reviewed in Hales et al. , 1997).…”
Section: The Identification Origin Taxonomy and Distribution Of Asementioning
confidence: 99%
“…However, aphid allozyme studies have revealed low levels of genetic polymorphism and correspondingly low levels of heterozygosity (Tomiuk & Wöhrmann, 1980; Loxdale et al. , 1985; Brookes & Loxdale, 1987; Tomiuk, 1987; Loxdale & Brookes, 1988, 1990; Simon & Hebert, 1995; reviewed in Hales et al. , 1997).…”
Section: The Identification Origin Taxonomy and Distribution Of Asementioning
confidence: 99%
“…on new hosts in the case of aphids), perhaps on a microgeographical scale (Guttman, 1997; Mopper & Strauss, 1998), selective sweeps rapidly purge populations of many of the genotypes present. When this happens, a rather structured population is likely to result, as with insecticide‐resistant aphids (Brookes & Loxdale, 1987; Foster et al. , 2000), with relatively few main genotypes, and with an initially reduced capability to undergo further immediate adaptive switches.…”
Section: Clones – Imaginary and Realmentioning
confidence: 99%
“…Like many aphids, population studies of M. persicae using allozyme markers have found little to no genetic variation (May and Holbrook, 1978;Wool et al, 1978;Brookes and Loxdale, 1987;Hales et al, 1997). In fact, in M. persicae, the only loci that have been found to be polymorphic are the esterase loci.…”
Section: Previous Population Studies In Myzus Persicaementioning
confidence: 99%